Online shipment scheduling expert system / Mohd Fairuz Mohd Shamsuri - Mohd Shamsuri, Mohd Fairuz (2005)
Scheduling is a normal day operations that human are used to already. Despite its nomfiality, it is not easy to arrange such arrangement. Even though scheduling has been done manually through out many years, but with the break through of technology, such operation can now be done machine. Shipping company usually handled hundreds or maybe thousands of transactions per day. As a haulage company, it is important for them to keep up their pace to be able to handle hundreds of data given the situation. The main purpose of this research to develop an online expert system that will help the top management to list out the suitable prime mover and its driver based on the data and rules. Currently there is no such system that running online. To develop this expert system, the researcher has set up an interview and series of discussion with the representation from the haulage company itself